Directional separation of hydrogen-containing gas mixture by hydrate-membrane coupling method. (15th April 2022) - Sun, Qiang; Yuan, Gaoqiang; Liu, Zheng; Gao, Jingbo; Wang, Yiwei; Guo, Xuqiang; Yang, Lanying
Abstract: Recovery of hydrogen (H2 ) from H2 -containing gas mixtures has great significance for energy conservation, cost reduction and benefit increase. However, the common separation methods have the ubiquitous problem due to phase equilibrium principle and results in the conflict between H2 concentration and H2 recovery rate in the product gas. Consequently, an innovative conception of hydrate-membrane coupling approach is proposed in this work. In the separation process, hydration and membrane permeation two separation driving forces coexist to achieve the aim of strengthening mass transfer kinetics. H2 and non-H2 components (hydrocarbons) are synchronously and directionally selected by membrane and hydrate to improve different phase compositions. Therefore, the gas in feed side could keep relatively high two separation driving forces (H2 fugacity and hydrocarbons fugacity). The results show that the coupling method could synchronously increase both the concentration and the recovery rate of H2 in the product gas. At the same time, the volume and concentration of the hydrocarbons in hydrate both increases effectively. It indicates that hydrate and membrane separation methods support each other in the separation process. The hydrate-membrane coupling method fundamentally solves the issue of the decreasing driving force resulting from single separation method and phase equilibrium relationship. Graphical abstract: Fig. 1 . The schematic diagram of directional separation of H2 -containing gas mixture using hydrate-membrane coupling method. (a) Before separation. (b) After separation. Image 1 Highlights: We proposed a coupling separation mechanism based on coexistence of two mass transfer processes. Hydrate-membrane coupling method was used to directionally separate H2 -containing gas mixture. The coupling separation method could synchronously increase the concentration and recovery of H2 . Coupling separation method breaks through the constraint of single phase equilibrium relation.